Parents–school relationship in the Dombóvár Inner City Primary School and Elementary Art Institution - Szabóné Szőke, Zsuzsanna (Acta Scientiarum Socialium, 2014)
Parents–school relationship in the Dombóvár Inner City Primary School and Elementary Art Institution According to the changes of our surroundings the requirements and the expectations in connection towards the school are also changing. During my work as a teacher I have often made notices about the connection of the parents and the school. To ease the work of all of us I chose the topic and made a questionnaire with the help of which I have examined the requirements and expectations of the parents towards the school, the quality of the relationship between the family and our school, and also the opportunities for improvement. My aim was to compare and contrast the conclusions gathered during my work and my personal experiences concerning the opinion of the parents, and knowing the data more precisely I also intended to increase the effectiveness of the pedagogical activity in our school.